ETIKA BISNIS DALAM PERSPEKTIF ISLAM (Fokus Ekonomi, 2010)
There is no ethic in business can make a destroy in a live. Because of that, many Businessman aware. Now, business ethic is a trend.The fact indicate that there is positif relation between perform and ethic. In Islam, business ethic explained in Al-Qur’an and Hadits. History about Nabi Muhammad saw said that Nabi is a successful businessman with Islamic ethic. Be based on the law in Islam, there are five principles in Islamic ethic.Keywords: business, ethic, perform ,law, principles